Effect of inoculation on water and salt distribution and alfalfa growth of coal gangue reconstructed layer - Gengchen LIU; Zengming KE; Yinli BI (Shuiwen dizhi gongcheng dizhi)
In the arid and semi-arid regions of western China, water scarcity and soil salinization pose significant constraints. These areas are also the primary sites for coal mining, where large amounts of coal gangue are generated during extraction occupying vast land resources, further exacerbating ecological degradation. Soil layer reconstruction and microbial remediation technologies are critical approaches for ecological restoration in mining dumps. However, the potential of coal gangue as a reconstructed soil layer material and its combined effects with microbial remediation remain unclear. This study investigated the impacts of different culvert layer materials (sandy soil and coal gangue) and Arbuscular mycorrhizal fungi (AMF) inoculation on soil water-salt distribution and alfalfa growth within a three-layer sponge structure (ecological layer-culvert layer - waterproof layer). Indoor soil column experiments were conducted with four treatments: sandy culvert layer without inoculation (S-CK), coal gangue culvert layer without inoculation (C-CK), sandy culvert layer with AMF inoculation (S-AM), and coal gangue culvert layer with AMF inoculation (C-AM), each with three replicates. Compared to the S-CK treatment, the C-CK treatment reduces surface soil salinity by 31.5%, while increasing alfalfa aboveground and belowground biomass by 49.6% and 38.3%, respectively. (2) Compared to the C-CK treatment, the C-AM treatment enhances aboveground and belowground biomass by 3.8-fold and 2.5-fold, respectively, but increased surface soil salt accumulation by 24.7%. AMF inoculation also promotes the development of coarse roots in the 20−40 cm soil layer. (3) The synergistic combination of coal gangue culvert layer and AMF inoculation increased soil moisture content in the ecological layer by 16.5%, reduces surface soil salinity by 14.5%, and elevates aboveground and belowground biomass by 4.1-fold and 4.7-fold, respectively. These findings demonstrate that the integration of coal gangue as a culvert layer with AMF inoculation creates a favorable soil water-salt environment, offering an effective strategy for mitigating salinization and promoting ecological restoration of open-pit mining dumps in western China.